Preparation method for optimizing PLA / PBS composite material based on interface strengthening compatibilization reaction
By introducing high-efficiency compatibility agents and controlling the capacity-enhancing reaction, the compatibility of PLA/PBS composites is significantly improved, and the problems of poor compatibility and poor performance are solved, achieving higher toughness, thermal stability and lowering production costs.
Patent Information
- Application Number
- CN202411776338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The poor compatibility of existing PLA/PBS composites leads to poor overall performance, especially in terms of toughness and thermal stability, while the preparation process is complex and costly.
By introducing high-efficiency compatibility agents, the epoxy groups react with the terminal hydroxyl groups of PLA and PBS, the molecular interaction force of the two is enhanced, and the compatibility of PLA/PBS composites is significantly improved by precisely controlling the degree of capacity-enhancing reaction.
The toughness and thermal stability of PLA/PBS composite materials are significantly improved, while maintaining their rigidity, processing fluidity and optical properties, reducing production costs and simplifying the preparation process.
Smart Images

Figure HDA0005171553620000011 
Figure HDA0005171553620000012 
Figure HDA0005171553620000013
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a composite material, in particular to a method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization. Background Art
[0002] Polylactic acid (PLA) is an eco-friendly, fully degradable polymer with good mechanical properties, excellent physical properties and good thermal stability. It is easy to process and compatible with the production processes of most common plastics. As an environmentally friendly material that is fully biodegradable and has low carbon emissions, PLA is widely used in medicine, biology, packaging and film. However, PLA also has some disadvantages, such as excessive rigidity, poor toughness, low crystallinity, high production temperature and high cost, which limit its application in other fields.
[0003] Among many biodegradable materials, polybutylene succinate (PBS) has attracted attention due to its excellent toughness and biocompatibility. Blending PBS with PLA can effectively improve the brittleness of PLA while maintaining its biodegradability and biocompatibility. However, the compatibility between PLA and PBS is poor, resulting in poor overall performance of simple blends of the two. Generally, compatibilizers can be introduced to improve the compatibility of the PLA / PBS system, and the bonding force between the interfaces can be enhanced through a compatibilization reaction, thereby achieving a better toughening effect. Although a variety of compatibilizers have been studied, the current research on how the degree of compatibilization reaction specifically affects the performance of PLA / PBS blends is still insufficient.
[0004] Publication patent CN116897184A relates to a PLA / PBS composite biodegradable material and its preparation process, which uses a variety of additives to improve the composite effect of PLA and PBS. However, there are certain limitations in improving the comprehensive performance of the material. For example, the elongation at break of the material only increases from the initial 55% to about 90%, and the improvement is limited. At the same time, due to the complex additive formula and cumbersome preparation process, the production cost is high.
[0005] Patent CN113265132A discloses a composite dynamically cross-linked PLA / PBS / NR / starch elastomer and its preparation method, which improves the compatibility of the materials by blending PLA, PBS and starch and adding a coupling agent. However, the mechanical properties of the material are limited, especially the tensile strength is only slightly improved, and the increase is not obvious.
[0006] Patent CN113045872A discloses a biodegradable PLA modified material with high heat resistance and high toughness and a preparation method thereof. The method adds PBS to PLA and introduces a compatibilizer to improve compatibility. Compared with pure PLA, the Vicat softening point temperature of the prepared modified material is increased, but the toughness improvement is limited, the elongation at break is only 30.82%, and the tensile strength is reduced from 60MPa to 37.32MPa. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing a PLA / PBS composite material based on an interface strengthening and compatibilization reaction optimization. The high-efficiency compatibilizer used in the present invention reacts with the terminal hydroxyl group in the blending system through its epoxy group, thereby enhancing the molecular interaction force between the two phases of PLA and PBS. By accurately controlling the degree of the compatibilization reaction, the compatibility of the two phases is significantly improved. This not only improves the toughness and thermal stability of the material, but also effectively maintains its rigidity, processing fluidity and optical properties. Required raw materials are easy to obtain, non-toxic and safe, and have low production cost. In addition, the preparation process is simple and the operation steps are convenient.
[0008] The objective of the present invention is achieved through the following technical solutions: A method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization, the method comprising the following preparation process: The dried PLA, PBS, high-efficiency compatibilizer, initiator and antioxidant are uniformly mixed; added into a twin-screw extruder for melt blending, the heating temperature of the twin-screw extruder is set to 150-220° C., the screw speed is 40-80 r / min, and the feeding speed is 5-10 r / min. The composite material obtained by melt blending is cooled in a water bath and granulated, and then dried in a vacuum oven at 60° C. for 12 hours for standby use; wherein the weight parts of the PLA / PBS composite material are as follows: Polylactic acid 50-90 parts; 10-50 parts of polybutylene succinate; High-efficiency compatibilizer 1-10 parts; Initiator 0.1-0.15 parts; Antioxidant 0.1-0.5 parts.
[0009] The invention discloses a method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization, wherein the high-efficiency compatibilizer is one or more of polyethylene grafted maleic anhydride (PE-8-MAH), polypropylene glycol sebacate citrate (PPSC), 2,2'-(1,3-phenylene)-bisoxazoline (BOZ), tributyl citrate (TBC), acetyl tributyl citrate (ATBC), dibutyl itaconate (DBI), and triphenylmethane tetraisocyanate (DTTI).
[0010] The method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization is described, wherein the initiator of the melt blending reaction is one or more of lauroyl peroxide (LPO), azobisisobutyronitrile (AIBN), dicumyl peroxide (DCP), acrylamide (AM), and tert-butyl perbenzoate (TBPB).
[0011] The method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization is described, wherein the antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 2,6-di-tert-butyl-4-methylphenol.
[0012] The advantages and effects of the present invention are: 1. The present invention introduces a compatibilizer to increase the intermolecular force between the two phases of PLA and PBS. The obtained composite material has better impact strength and elongation at break than the PLA / PBS material. While improving the toughness of the composite material, it also maintains its rigidity well and exhibits relatively excellent optical properties and heat resistance.
[0013] 2. The present invention uses flexible biodegradable materials to improve the toughness of PLA, which can alleviate the problem of white pollution caused by petroleum-based plastics to a certain extent. The required raw materials are easy to obtain, non-toxic and safe, and the production cost is low. The production process of the present invention is simple and highly operable, which further broadens the scope of application of PLA composite materials in industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a graph showing the effect of the amount of compatibilizer added on the impact strength of the PLA / PBS blend material of the present invention; Figure 2 The figure is the effect of the amount of compatibilizer added on the tensile strength and elongation at break of PLA / PBS blends of the present invention; Figure 3 This is a graph showing the effect of the amount of compatibilizer added on the thermal properties of the PLA / PBS blend material of the present invention; Figure 4 This is a graph showing the effect of the amount of compatibilizer added on the transmittance and melt index of the PLA / PBS blend. DETAILED DESCRIPTION
[0015] The present invention is described in detail below through specific examples. It should be noted that these examples are only used to illustrate the present invention and do not limit the scope of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention without departing from the basic principles of the present invention, and these improvements and adjustments should also be regarded as part of the protection scope of the present invention.
[0016] Embodiments 1-5 are embodiments of the present invention respectively, and the present invention is described in detail below in conjunction with the embodiments.
[0017] Comparative Example 1 80 parts of polylactic acid; 20 parts of polybutylene succinate; 0.15 parts of initiator; Antioxidant 0.1 part.
[0018] According to the number of materials, PLA, PBS, initiator DCP, and antioxidant 1010 were uniformly mixed, and the mixture was sent to a twin-screw extruder for melt blending. The temperature of each zone of the extruder was set as follows: zone I was 165°C, zone II to zone V were 175°C, the die was 160°C, the screw speed was set to 60r / in, and the feed rate was 8.0r / min. The composite material strips were cooled in water and pelletized, and placed in a vacuum oven at 60°C for 12 hours.
[0019] The final blend sample was added to a micro injection molding machine, the barrel temperature was set to 180°C, the mold temperature was set to 50°C, the holding time was 10s, and the sample was injection molded into a tensile specimen according to the national standard GB / T1040.2-2006. The dried sample was added to a micro injection molding machine, the barrel temperature was set to 175°C, the mold temperature was set to 50°C, the holding time was 10s, and the sample was injection molded into an impact specimen according to the national standard GB / T1843-2008. The elongation at break, impact strength and tensile strength of the material were tested in accordance with the GB / T1040.2-2006 and GB / T1043.1-2008 test standards.
[0020] PLA / PBS blend samples (6-8 mg) were placed in a crucible for DSC thermal property testing.
[0021] The PLA / PBS blend samples were pressed into films with a thickness of about 80 μm using a flat plate vulcanizer, and the transmittance of the materials was tested using a haze meter (CS-700).
[0022] The flow properties of the blends were measured using a melt flow rate meter (GT-7100-MH) at 190° C. and a load of 2.16 kg according to the test standard ASTM D1238-2013. Example 1
[0023] 80 parts of polylactic acid; 20 parts of polybutylene succinate; 1 part of compatibilizer; 0.15 parts of initiator; Antioxidant 0.1 part.
[0024] According to the number of materials, PLA, PBS, compatibilizer BOZ, initiator DCP, and antioxidant 1010 were uniformly mixed, and the mixture was sent to a twin-screw extruder for melt blending. The temperature of each zone of the extruder was set as follows: zone 165°C, zone II to zone V 175°C, and die head 160°C. The screw speed was set to 60r / min, and the feed rate was 8.0r / min. The composite material strips were cooled in water and granulated, and placed in a vacuum oven at 60°C for 12 hours.
[0025] The prepared composite material pellets were placed in a WZS10D micro injection molding machine, and the standard tensile specimens and impact standard specimens were made at a barrel temperature of 175°C, a mold temperature of 40°C, and a holding time of 10s. The excess parts of the specimens were trimmed, and finally the tensile performance test and impact performance test were carried out. Tensile performance test: The samples were made according to the GB / T 1040.2-2022 / 1BA standard, and then stretched at a tensile rate of 20mm / min using a tensile testing machine to measure the tensile strength and elongation at break of the samples. Impact performance test: The samples were made according to the GB / T 1843-2008 / A standard, and then the impact strength of the samples was measured using an impact strength testing machine with an initial pendulum angle of 150° and an initial dynamic potential energy of 2.750J.
[0026] PLA / PBS blend samples (6-8 mg) were placed in a crucible for DSC thermal property testing.
[0027] The prepared composite material particles were pressed into a film of about 80 μm thick using a flat vulcanizer at a pressure of 10 MPa, and then the transmittance thereof was tested using a haze meter.
[0028] The melt flow index was measured using a GT-7100-MH melt flow indexer at 190°C and 2.16 kg (test standard: ASTM D1238-2013). Example 2
[0029] 80 parts of polylactic acid; 20 parts of polybutylene succinate; 2 parts of compatibilizer; 0.15 parts of initiator; Antioxidant 0.1 part.
[0030] According to the number of materials, PLA, PBS, compatibilizer BOZ, initiator DCP, and antioxidant 1010 were uniformly mixed, and the mixture was sent to a twin-screw extruder for melt blending. The temperature of each zone of the extruder was set as follows: zone 1 was 165°C, zone II to zone V were 175°C, and the die was 160°C. The screw speed was set to 60r / min, and the feed rate was 8.0r / min. The composite material strips were cooled in water and granulated, and placed in a vacuum oven at 60°C for 12 hours.
[0031] The prepared composite material pellets were placed in a WZS10D micro injection molding machine, and the standard tensile specimens and impact standard specimens were made at a barrel temperature of 175°C, a mold temperature of 40°C, and a holding time of 10s. The excess parts of the specimens were trimmed, and finally the tensile performance test and impact performance test were carried out. Tensile performance test: The samples were made according to the GB / T 1040.2-2022 / 1BA standard, and then stretched at a tensile rate of 20m / min using a tensile testing machine to measure the tensile strength and elongation at break of the samples. Impact performance test: The samples were made according to the GB / T 1843-2008 / A standard, and then the impact strength of the samples was measured using an impact strength testing machine with an initial pendulum angle of 150° and an initial dynamic potential energy of 2.750J.
[0032] PLA / PBS blend samples (6-8 mg) were placed in a crucible for DSC thermal property testing.
[0033] The prepared composite material particles were pressed into a film of about 80 μm thick using a flat vulcanizer at a pressure of 10 MPa, and then the transmittance thereof was tested using a haze meter.
[0034] The melt flow index was measured using a GT-7100-MH melt flow indexer at 190°C and 2.16 kg (test standard: ASTM D1238-2013). Example 3
[0035] 80 parts of polylactic acid; 20 parts of polybutylene succinate; 3 parts of compatibilizer; 0.15 parts of initiator; Antioxidant 0.1 part.
[0036] According to the number of materials, PLA, PBS, compatibilizer BOZ, initiator DCP, and antioxidant 1010 were uniformly mixed, and the mixture was sent to a twin-screw extruder for melt blending. The temperature of each zone of the extruder was set as follows: zone 1 was 165°C, zone II to zone V were 175°C, and the die was 160°C. The screw speed was set to 60r / min, and the feed rate was 8.0r / min. The composite material strips were cooled in water and granulated, and placed in a vacuum oven at 60°C for 12 hours.
[0037] The prepared composite material pellets were placed in a WZS10D micro injection molding machine, and the standard tensile and impact specimens were made at a barrel temperature of 175°C, a mold temperature of 40°C, and a holding time of 10s. The excess parts of the specimens were trimmed, and finally the tensile performance test and impact performance test were performed. Tensile performance test: The sample was made according to the GB / T 1040.2-2022 / 1BA standard, and then stretched at a tensile rate of 20m / min using a tensile testing machine to measure the tensile strength and elongation at break of the sample. Impact performance test: The sample was made according to the GB / T 1843-2008 / A standard, and then the impact strength of the sample was measured using an impact strength testing machine with an initial pendulum angle of 150° and an initial dynamic potential energy of 2.750J.
[0038] PLA / PBS blend samples (6-8 mg) were placed in a crucible for DSC thermal property testing.
[0039] The prepared composite material particles were pressed into a film of about 80 μm thick using a flat vulcanizer at a pressure of 10 MPa, and then the transmittance thereof was tested using a haze meter.
[0040] The melt flow index was measured using a GT-7100-MH melt flow indexer at 190°C and 2.16 kg (test standard: ASTM D1238-2013). Example 4
[0041] 80 parts of polylactic acid; 20 parts of polybutylene succinate; 4 parts of compatibilizer; 0.15 parts of initiator; Antioxidant 0.1 part.
[0042] According to the number of materials, PLA, PBS, compatibilizer BOZ, initiator DCP, and antioxidant 1010 were uniformly mixed, and the mixture was sent to a twin-screw extruder for melt blending. The temperature of each zone of the extruder was set as follows: zone 1 was 165°C, zone II to zone V were 175°C, and the die was 160°C. The screw speed was set to 60r / min, and the feed rate was 8.0r / min. The composite material strips were cooled in water and granulated, and placed in a vacuum oven at 60°C for 12 hours.
[0043] The prepared composite material pellets were placed in a WZS10D micro injection molding machine, and the standard tensile and impact specimens were made at a barrel temperature of 175°C, a mold temperature of 40°C, and a holding time of 10s. The excess parts of the specimens were trimmed, and finally the tensile performance test and impact performance test were performed. Tensile performance test: The sample was made according to the GB / T 1040.2-2022 / 1BA standard, and then stretched at a tensile rate of 20m / min using a tensile testing machine to measure the tensile strength and elongation at break of the sample. Impact performance test: The sample was made according to the GB / T 1843-2008 / A standard, and then the impact strength of the sample was measured using an impact strength testing machine with an initial pendulum angle of 150° and an initial dynamic potential energy of 2.750J.
[0044] PLA / PBS blend samples (6-8 mg) were placed in a crucible for DSC thermal property testing.
[0045] The prepared composite material particles were pressed into a film of about 80 μm thick using a flat vulcanizer at a pressure of 10 MPa, and then the transmittance thereof was tested using a haze meter.
[0046] The melt flow index was measured using a GT-7100-MH melt flow indexer at 190°C and 2.16 kg (test standard is ASTM D1238-2013). Example 5
[0047] 80 parts of polylactic acid; 20 parts of polybutylene succinate; 5 parts of compatibilizer; 0.15 parts of initiator; Antioxidant 0.1 part.
[0048] According to the number of materials, PLA, PBS, BOZ, initiator DCP, and antioxidant 1010 were uniformly mixed, and the mixture was sent to a twin-screw extruder for melt blending. The temperature of each zone of the extruder was set as follows: zone 1 was 165°C, zone II to zone V were 175°C, and the die was 160°C. The screw speed was set to 60r / min, and the feed rate was 8.0r / min. The composite material strips were cooled in water and granulated, and placed in a vacuum oven at 60°C for 12 hours.
[0049] The prepared composite material pellets were placed in a WZS10D micro injection molding machine, and the standard tensile and impact specimens were made at a barrel temperature of 175°C, a mold temperature of 40°C, and a holding time of 10s. The excess parts of the specimens were trimmed, and finally the tensile performance test and impact performance test were carried out. Tensile performance test: The sample was made according to the GB / T 1040.2-2022 / 1BA standard, and then stretched at a tensile rate of 20m / min using a tensile testing machine to measure the tensile strength and elongation at break of the sample. Impact performance test: The sample was made according to the GB / T 1843-2008 / A standard, and then the impact strength of the sample was measured using an impact strength testing machine with an initial pendulum angle of 150° and an initial dynamic potential energy of 2.750J.
[0050] PLA / PBS blend samples (6-8 mg) were placed in a crucible for DSC thermal property testing.
[0051] The prepared composite material particles were pressed into a film of about 80 μm thick using a flat vulcanizer at a pressure of 10 MPa, and then the transmittance thereof was tested using a haze meter.
[0052] The melt flow index was measured using a GT-7100-MH melt flow indexer at 190°C and 2.16 kg (test standard: ASTM D1238-2013).
[0053] The mechanical properties of the composite material samples prepared in the comparative example and the embodiment were tested respectively. Figure 1 This is the effect of the amount of compatibilizer added on the impact strength of PLA / PBS blends; Figure 2 This is a graph showing the effect of compatibilizer addition on the tensile strength and elongation at break of PLA / PBS blends.
[0054] Table 1. Mechanical properties test results of PLA / PBS blends <![CDATA[Impact strength (J / m 2 )]]> Tensile strength(MPa) Elongation at break (%) Comparative Example 1 3126.5 50.74 109 Example 1 5881.2 51.27 110.41 Example 2 7215.6 49.95 207.44 Example 3 7990.6 52.11 273.81 Example 4 6715.6 51.69 148.57 Example 5 5965.6 49.75 101.78 As can be seen from Table 1, the high-efficiency compatibilizer significantly improves the compatibility of PLA and PBS, reduces the phase separation phenomenon of the two, and significantly enhances the mechanical properties of PLA / PBS blends, especially in terms of impact strength and elongation at break. While keeping the tensile strength substantially unchanged, the impact strength and elongation at break of specific embodiment 3 reached 7990.6J / m² and 273.81%, respectively, which are 2.6 times and 2.5 times of the PLA / PBS blend without the volume expansion reaction. Therefore, the volume expansion reaction can effectively improve the mechanical properties of the PLA / PBS blend and broaden its scope of application.
[0055] The composite material samples prepared in the comparative example and the embodiment were respectively subjected to DSC thermal performance tests. Figure 3 This is a graph showing the effect of the amount of compatibilizer added on the thermal properties of PLA / PBS blends.
[0056] Table 2 Thermal properties of PLA / PBS blends <![CDATA[T g (PLA) / ℃]]> <![CDATA[T m (PBS) / ℃]]> <![CDATA[T m (PLA) / ℃]]> <![CDATA[T c (PBS) / ℃]]> Comparative Example 1 57.91 113.02 149.85 67.46 Example 1 57.19 112.62 146.72 68.64 Example 2 56.17 112.12 146.05 63.97 Example 3 55.93 111.77 145.21 65.98 Example 4 54.34 111.31 144.28 69.29 Example 5 53.61 111.88 144.08 80.19 From the data in the table, it can be seen that the glass transition temperature of the blend in Example 1 dropped to 57.19°C, while the glass transition temperature of the PLA component in the blend in Example 5 dropped to 53.61°C. Figure 2 It can also be observed that with the increase of the degree of compatibilization reaction, the melting behavior of PLA / PBS / BOZ blends changes, which is manifested in the increase and broadening of the melting peak and cold crystallization peak.
[0057] Through the above analysis, it can be concluded that the degree of compatibilization reaction significantly affects the crystallization behavior of PLA / PBS blends, which is manifested in the gradual increase of crystallization temperature and the enhancement of crystallization ability. At the same time, with the increase of the degree of compatibilization reaction, the compatibility between the blends is improved, and the influence of the improved compatibility on the crystallization behavior is gradually increased.
[0058] The composite material samples prepared in the comparative example and the embodiment were tested for transmittance and melt flow rate. Figure 4 This is a graph showing the effect of the amount of compatibilizer added on the permeability and melt index of PLA / PBS blends.
[0059] Table 3. Transmittance and melt index data of PLA / PBS blends Transmittance(%) Melt flow rate (g / 10min) Comparative Example 1 81.3 6.9 Example 1 87.1 3.5 Example 2 90.1 4.1 Example 3 91.0 4.3 Example 4 91.0 4.7 Example 5 87.9 5.5 As can be seen from the data in the table, the transmittance of the blend is closely related to the amount of high-efficiency compatibilizer added. With the increase in the amount of high-efficiency compatibilizer added, the transmittance of the system is increased from 81.3% to about 90%. At the same time, the melt fluidity of BOZ and PLA / PBS blends also increases with the increase in the degree of compatibilization reaction, and the component of Example 5 shows the best fluidity.
[0060] The description of the above embodiments is only used to help understand the method of the present invention and its core concept. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The above embodiments are only intended to facilitate the clear description of the method of the present invention and its core concept. Professionals should understand that technical improvements and changes can be made to the present invention without departing from the principles and spirit disclosed by the present invention. These corresponding improvements and changes should also be regarded as the scope of protection covered by the claims of the present invention.
Claims
1. A method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization, characterized in that: The method comprises the following preparation process: The dried PLA, PBS, high-efficiency compatibilizer, initiator and antioxidant are uniformly mixed; added into a twin-screw extruder for melt blending, the heating temperature of the twin-screw extruder is set to 150-220° C., the screw speed is 40-80 r / min, and the feeding speed is 5-10 r / min. The composite material obtained by melt blending is cooled in a water bath and granulated, and then dried in a vacuum oven at 60° C. for 12 hours for standby use; wherein the weight parts of the PLA / PBS composite material are as follows: Polylactic acid 50-90 parts; 10-50 parts of polybutylene succinate; High-efficiency compatibilizer 1-10 parts; Initiator 0.1-0.15 parts; Antioxidant 0.1-0.5 parts.
2. The method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization according to claim 1, characterized in that: The high-efficiency compatibilizer is one or more of polyethylene grafted maleic anhydride (PE-8-MAH), polypropylene glycol sebacate citrate (PPSC), 2,2'-(1,3-phenylene)-bisoxazoline (BOZ), tributyl citrate (TBC), acetyl tributyl citrate (ATBC), dibutyl itaconate (DBI), and triphenylmethane tetraisocyanate (DTTI).
3. A method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization according to claim 1, characterized in that: The initiator of the melt blending reaction is one or more of lauroyl peroxide (LPO), azobisisobutyronitrile (AIBN), dicumyl peroxide (DCP), acrylamide (AM), and tert-butyl perbenzoate (TBPB).
4. A method for preparing a PLA / PBS composite material based on interface strengthening and compatibilization reaction optimization according to claim 1, characterized in that: The antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 2,6-di-tert-butyl-4-methylphenol.
Citation Information
Patent Citations
Biodegradable PLA modified material with high heat resistance and high toughness and preparation method thereof
CN113045872A
Composite dynamic crosslinking PLA / PBS / NR / starch elastomer and preparation method thereof
CN113265132A
Biopolymer compositions containing additives
CN116897184A
Modified polylactic material for 3D (three dimensional) printing and preparation method thereof
CN104530669A
High-toughness heat-resistant biodegradable composite material for tableware and preparation method thereof
CN113185821A